The effect of a knee brace on gait parameters of hypertonic hemiplegic patients - M.R. Modisane; A. Stewart; M. Riley (AOSIS, 2008)
The aim of this study was to investigate the effects of the useof a knee brace on 15 subjects with hypertonic hemiparesis. The middlecerebral artery was involved in all subjects. The Ashworth scale was usedto screen for the presence of spasticity in the quadriceps muscles.Measurements of gait speed, step and stride length were taken in the middle 10 metres of a 15 metre paper walkway. A comparison of these gait parameters without and with the use of a knee brace was made. A ques-tionnaire was also used to evaluate how subjects responded to the use of aknee brace.The results showed that the mean speed for all 15 subjects increased withthe use of a brace, (p = 0.05). Step and stride length without and with the use of a brace showed no statistical differences.It was therefore concluded that the FECK brace appears to have an effect on the walking speed of subjects withhypertonic  hemiparesis